2018
DOI: 10.30997/dt.v5i1.1110
|View full text |Cite
|
Sign up to set email alerts
|

English Learning Based on Multiple Intelligence in Type of Linguistic Intelligence

Abstract: This study aims to describe the application of English language learning based on Multiple Intelligence Theory on the type of linguistic intelligence and student responses in following the learning of English. This research is a descriptive research, conducted in Madrasah Ibtidaiyah Muhammadiyah Special Program Kartasura. Respondents in this study were principals, English language teachers, and 34 students. Data were collected through interview (semi-structured interview), observation, and questionnaire. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…⋅ Linguistic involves the ability to learn languages, sensitivity to spoken and written language, and the capacity to use language effectively to express oneself either rhetorically or poetically [29,76,107]. ⋅ Logical-mathematical consists of the capacity to carry out scientific research, mathematical operations, as well as to analyze problems logically [10,12].…”
Section: Pedagogical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…⋅ Linguistic involves the ability to learn languages, sensitivity to spoken and written language, and the capacity to use language effectively to express oneself either rhetorically or poetically [29,76,107]. ⋅ Logical-mathematical consists of the capacity to carry out scientific research, mathematical operations, as well as to analyze problems logically [10,12].…”
Section: Pedagogical Frameworkmentioning
confidence: 99%
“…Therefore, teaching individual's intelligence strengths will provide a more productive learning environment and produce a more receptive student. The eight intelligences are described as follows [91]: Linguistic involves the ability to learn languages, sensitivity to spoken and written language, and the capacity to use language effectively to express oneself either rhetorically or poetically [29, 76, 107]. Logical‐mathematical consists of the capacity to carry out scientific research, mathematical operations, as well as to analyze problems logically [10, 12].…”
Section: Pedagogical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, teachers' teaching methods and approaches may not match learners' expectations, leading to inefficient teaching and learning [29]. Another obstacle is the lack of appropriate activities and environmental interactions in the curriculum, which hinders the development of MI-based learning materials [30]. Based on the results of these previous researches, it can be concluded that teachers still have difficulty developing their creativity in developing the quality of thematic learning outcomes based on multiple intelligences of MI students.…”
Section: Introductionmentioning
confidence: 99%
“…While the previous study such as from Fortuna (2019) only focused on students' linguistic intelligence, not on English linguistic intelligence. The second study was conducted from Pradana ( 2018) that only focused on English learning in the type of linguistic intelligence but did not specifically mention the linguistic indicators. The last study was conducted by Vincey (2016) that only focused on Linguistic intelligence and Students' Academic Achievement.…”
Section: Introductionmentioning
confidence: 99%